2018
DOI: 10.3390/su10114051
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Focus of Structural Reform in China?—Comparison of the Factor Misallocation Degree within the Manufacturing Industry with a Unified Model

Abstract: The misallocation of production factors, with structural misallocation as an important aspect, is a key instigator of low total factor productivity (TFP) growth rate in China, but one important question is which structural misallocation of what factor is more serious in China. Using China’s manufacturing industrial enterprise data from 1998 to 2013, we calculated and compared the factors misallocation degree among industries, ownerships and regions. The results indicated that, the misallocation among industrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 35 publications
0
21
0
Order By: Relevance
“…It is relevant to note that, due to the neglecting or mis-measuring adjustment costs, neglecting differences in technologies across establishments, etc., it may lead to an excessive exaggeration of the misallocation degree of resources [48]. The above research basically affirms that gap between China and developed countries is widening because of resource misallocation, and is an important constraint to the high-quality development of China's economy [13,48,49].…”
Section: Literature Reviewmentioning
confidence: 58%
“…It is relevant to note that, due to the neglecting or mis-measuring adjustment costs, neglecting differences in technologies across establishments, etc., it may lead to an excessive exaggeration of the misallocation degree of resources [48]. The above research basically affirms that gap between China and developed countries is widening because of resource misallocation, and is an important constraint to the high-quality development of China's economy [13,48,49].…”
Section: Literature Reviewmentioning
confidence: 58%
“…Many factors such as local protectionism and government intervention [2,3], ownership differences caused by administrative monopolies [4,5], firm-level policy distortions [6,7], and imbalanced development of transportation infrastructure [8] has been causing serious resource misallocation in China. Under the theoretical framework of measuring the degree of resource misallocation developed by Hsieh and Klenow [9], domestic and foreign scholars have examined the current situation of resource misallocation in China from the aspect of industry, region and ownership [10,11]. Essential productive factors involved in the existing fruitful studies include capital, labor, land, energy, etc.…”
Section: Introductionmentioning
confidence: 99%
“…This may be due to the different types of enterprises examined. Based on the theory of enterprise heterogeneity, some scholars have reported that the impact of resource mismatching on TFP is negative [13][14][15], and some have discovered that it is positive [16]. China's furniture enterprises are typical in terms of the distortion of labor resources, and their exports are primarily composed of processing trade.…”
Section: Introductionmentioning
confidence: 99%